(De)construction of the meanings of work: experiences of suffering in hospital emergency wards - Santana, Thiago da Silva; Sousa, Anderson Reis de; Servo, Maria Lúcia Silva; Carneiro, Itamar de Almeida; Moreira, Wanderson Carneiro; Fontoura, Elaine Guedes; Souza, Kleyze Araújo de Oliveira (Revista de Enfermagem da UFPI, 2023)
Objective: To investigate the experiences of suffering in the work of nurses in a hospital emergency service. Methods: Qualitative study with 15 nurses from a public hospital emergency unit in a municipality in Bahia, Brazil. Data were obtained through in-depth interviews, analyzed by the Collective Subject Discourse and anchored in the theoretical framework of Work Psychodynamics. Results: There is professional suffering in the work of nurses in the Hospital Emergency Unit and it is permeated by the (de)construction of the meanings of work, the way work is organized, professional recognition, psychological illness, and the coping strategies developed and available to them. Final considerations: The suffering that emerges from work relationships presents specificities of the organization and professional practice in nursing in the emergency sector, which makes up the context, causes and consequences of the phenomenon and impacts on the different dimensions of life.